Implementation of Acceleration of Complete Systematic Land Registration (PTSL) at the Land Office of Kupang City, East Nusa Tenggara Province - Anastasya NINGRUM; Nursalam NURSALAM; Ajis S. Adang DJAHA (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to analyze the implementation of acceleration of Complete Systematic Land Registration (PTSL) at the Land Office of Kupang City, East Nusa Tenggara Province. Using a qualitative approach, this study focuses on the policy dimensions according to Merilee S. Grindle's theory, namely policy content and policy context. The results of the study indicate that although the benefits of the program have been felt by the community, especially the lower middle class, its implementation has not been fully effective. The main obstacle found was the lack of coordination and communication between the Land Office, sub-districts, and the community. Despite efforts to improve, such as more intensive coordination and going directly to the field, several sub-districts, including Manutapen Sub-district, still experience delays in socialization and measurement. This study suggests improving coordination between institutions and wider socialization to ensure that this program is right on target and can be felt by all levels of society.